2019
DOI: 10.33005/mebis.v4i1.46
|View full text |Cite
|
Sign up to set email alerts
|

Perceived Ease of Use Dan Perceived Usefulness Terhadap E-Commerce Intention Melalui Aplikasi Online Shop Pada Mahasiswa Di Surabaya

Abstract: Pertumbuhan e-commerce yang pesat dalam kurun waktu 4 tahun terakhir menjadi peluang bisnis yang sangat potensial di Indonesia. Peluang tersebut dapat menjadi alternatif solusi bagi pengangguran di Indonesia yang meningkat pada tahun 2017. Namun melihat bahwa industri digital tergolong industri yang padat modal, perlu kemudian kiranya dikaji kembali arah pemanfaatan peluang tersebut. Fokus dari penciptaan lapangan kerja sebaiknya tidak pada penciptaaan platform-platform e-commerce yang sem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
1
0
5

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 7 publications
4
1
0
5
Order By: Relevance
“…This finding was consistent with the previous research that showed the positive significant impact of perceived ease of use and attitude towards e-commerce intention (Almaimouni et al, 2014;Bennani & Oumlil, 2014;Hoque et al, 2015;Isaac et al, 2017;Suryawirawan, 2019). Although the result on perceived usefulness found to be inconsistent with the aforementioned extant corpus, some of the previous findings still showed similar results (Letchumanan & Muniandy, 2013;Suryawirawan, 2019). This result implied that rather than the usefulness of an application, the easiness of it and attitude towards it were the variables that determined its adoption.…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…This finding was consistent with the previous research that showed the positive significant impact of perceived ease of use and attitude towards e-commerce intention (Almaimouni et al, 2014;Bennani & Oumlil, 2014;Hoque et al, 2015;Isaac et al, 2017;Suryawirawan, 2019). Although the result on perceived usefulness found to be inconsistent with the aforementioned extant corpus, some of the previous findings still showed similar results (Letchumanan & Muniandy, 2013;Suryawirawan, 2019). This result implied that rather than the usefulness of an application, the easiness of it and attitude towards it were the variables that determined its adoption.…”
Section: Discussionsupporting
confidence: 92%
“…Lastly, among the antecedents of e-commerce adoption in this study, only perceived usefulness produced insignificant result, while perceived ease of use and attitude showed significant impact towards e-commerce adoption. This finding was consistent with the previous research that showed the positive significant impact of perceived ease of use and attitude towards e-commerce intention (Almaimouni et al, 2014;Bennani & Oumlil, 2014;Hoque et al, 2015;Isaac et al, 2017;Suryawirawan, 2019). Although the result on perceived usefulness found to be inconsistent with the aforementioned extant corpus, some of the previous findings still showed similar results (Letchumanan & Muniandy, 2013;Suryawirawan, 2019).…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations